Monetärer Keynesianismus: Versuch einer Rekonstruktion von Hajo Rieses "Theorie der Geldwirtschaft" - Peter Spahn (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2024)
Hajo Riese (FU Berlin) was a pioneer of the "Berlin School of Monetary Keynesianism", particularly in the 1980s and 1990s. His research work was based on the roots of monetary theory in the work of J. M. Keynes, with a particular focus on the theory of capital and interest rates. While in Keynes liquidity preference remained an element of money demand, for Riese it formed the central variable of a theory of credit supply. The credit contract is not based on goods or goods equivalents, but on the nominal category of money, because this is the sole medium for the fulfilment of contracts. In addition to the interest rate, the rate of return on real capital is also determined by the liquidity premium. The central bank has to take into account the regulatory-theoretical significance of monetary stability, which runs counter to the "easy money policy" usually demanded by Keynesians.
Keywords: 330; Keynesianismus; Monetarismus; Keynesianismus; Monetarismus